Pengaruh Kurs, BI 7 Day (Reverse) Rapo Rate dan Inflasi terhadap Indeks Harga Saham Gabungan pada Masa Pandemi Covid-19 - Dessyana Damayanti; Novi Permata Indah (Universitas Batanghari, 2022)
The purpose of this study was to examine the effect of the exchange rate, BI 7-day repo rate (BI7dRR), and inflation on the Jakarta Composite Index (JCI). Library and document methods were used in the data collection procedure. During the Covid-19 pandemic, this analysis uses 41 sample data obtained from Bank Indonesia and the Indonesia Stock Exchange during the period January 2019-May 2022. This study uses a quantitative descriptive method that includes multiple linear analysis. The rupiah exchange rate and the BI 7-day repo rate (BI7dRR) have a negative and significant effect on the Jakarta Composite Index during the Covid-19 pandemic, while inflation has a positive and significant impact on the Jakarta Composite Index during the Covid-19 pandemic, according to the results of SPSS 22 analysis.